2007
DOI: 10.1055/s-2007-980192
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Pituitary MRI has High Sensitivity and Specificity for the Diagnosis of Mild Cushing's Syndrome and should be Part of the Initial Workup

Abstract: We conclude that almost all patients in this series with Cushing's syndrome have a lesion on dynamic pituitary MRI, a rate much higher than the 50-60% rate reported for non-dynamic MRIs. The false positive rate of 16% in our group of Cushing's excluded patients is similar to the literature value of 10% seen in normal volunteers and is acceptable since MRI is not used solely as a determinant for the diagnosis. While a negative MRI will miss those patients with adrenal or ectopic Cushing's syndrome, those patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(41 citation statements)
references
References 20 publications
1
38
1
1
Order By: Relevance
“…In a recent review, Raff reported that measurement of an elevated late-night SC has a O90% sensitivity and specificity for the diagnosis of CS (11), while a recently published meta-analysis on SC measurement in CS took into account only seven studies that contained sufficient information to be processed (10). A total of 339 patients with CS revealed for SC a pooled sensitivity of 92% and a specificity of 96% (5,21,22,23,24,25,26). In our series, a cutoff of 2.77 ng/ml for MSC obtained a sensitivity of 100% to identify patients with CD untr and a specificity of 97.7% in the controls, the results being similar to those described in the literature (5,7,20,21,22,23,24,25,26,27,28,29,30,31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent review, Raff reported that measurement of an elevated late-night SC has a O90% sensitivity and specificity for the diagnosis of CS (11), while a recently published meta-analysis on SC measurement in CS took into account only seven studies that contained sufficient information to be processed (10). A total of 339 patients with CS revealed for SC a pooled sensitivity of 92% and a specificity of 96% (5,21,22,23,24,25,26). In our series, a cutoff of 2.77 ng/ml for MSC obtained a sensitivity of 100% to identify patients with CD untr and a specificity of 97.7% in the controls, the results being similar to those described in the literature (5,7,20,21,22,23,24,25,26,27,28,29,30,31).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 339 patients with CS revealed for SC a pooled sensitivity of 92% and a specificity of 96% (5,21,22,23,24,25,26). In our series, a cutoff of 2.77 ng/ml for MSC obtained a sensitivity of 100% to identify patients with CD untr and a specificity of 97.7% in the controls, the results being similar to those described in the literature (5,7,20,21,22,23,24,25,26,27,28,29,30,31). More limited data are available regarding the determination of SC after the DST and not always as reliable as MSC (22,28,31,32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, more detailed sequences (e.g., dynamic and/or SPGR MRI) are often employed, leading to a reported improvement in sensitivity from 50-55% (SE) to 70-75% (dynamic) and 70-90% (SPGR), but with the important caveat of a high detection rate of incidental pituitary lesions (6,20,21,22). This presents a significant challenge, with the risk that a coincidental pituitary lesion will be erroneously identified as the source of excess ACTH, either in a patient with genuine CD due to a non-visualised microadenoma (illustrative case 5, Fig.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…A study by Githinji KJ et al on clinical experience and outcome of pituitary surgery reported mean age of 36.9 + 14.6 years and they also found female preponderance (60.0%) in their study. 15,16 Another study by Seuk JW et al also found a similar age of presentation (42.4 years), however, they found in contrast gender presentation with males in dominance with (72.5%) proportion. 17,18 Gnjidic Z and colleagues reported mean age of 40.1 years ranging from 19 to 65 years.…”
Section: Discussionmentioning
confidence: 85%